Translation und Exil (1933–1945) II : Netzwerke des Übersetzens - Weber Henking, Irene 1964- HerausgeberIn; Dietiker, Pino 1991- HerausgeberIn; Rougemont, Marina HerausgeberIn (Transkulturalität – Translation – Transfer, 2023)
Translation does not work in a vacuum. Making it visible as action in a structured context is the goal of this book. This broad context includes individuals and, more significantly, collective actors-publishers, reviewers and patrons, publishers, journals, social and political organizations. Individually and collectively, they form dynamic, interactive, and interdependent networks. These are essential for translation in exile, as they influence the production and reception of translations both positively and negatively. If they are missing, not only working conditions change, but entire biographies. Newly emerging networks, on the other hand, create the conditions for translating. What are the working and living conditions, the structures of action and publication in which translations are produced? What roles do they play in the lives and aesthetic careers of individual translators in exile? Answers can be found in this book